(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Many successful organizations realize their employees as their greatest asset. Therefore, most HRs within the organization must recruit valuable candidates for the organization. The main purpose of the research is to research the activities of the sources of recruitment, performance appraisal, and employee retention activities taken by the talent acquisition team within the case of primary data, a structured questionnaire was prepared to know the importance of Talent Acquisition activities, which might be qualitative data, and send across 60 respondents randomly from all the HRs working in various IT services. In secondary data to assess the importance of sourcing the candidates, evaluation of Performance appraisal, Employee Retention activities and Employers mindset about Experience. The responses that we got from the varied HRs are collected and that we had taken out the results through percentage analysis, Correlation Tests, Regression Tests and Chi-Square Tests during which all the tests had been wiped out SPSS tools. Through these tests, we had some findings on the Talent Acquisition Activities of HRs working in various IT Sectors